Pengaruh Kegiatan Penyuluhan Kesehatan Reproduksi Terhadap Pengetahuan Dan Sikap Tentang Seksual Pranikah Remaja Desa Lebak Pracimantoro - Agustina Mar’atus Sholichah; Afifah Novita Yuliastuti; Terza Aflika Happy (2020)
Adolescence is a transition between childhood and adulthood characterized by psychic, physical change and maturation of human reproductive organs called puberty. Adolescent populations need to get serious attention because they are very risky with reproductive health issues about premarital sexual behavior, drugs and HIV/AIDS and have a great desire to try various things, including active in dating. The purpose of this research is to know the influence of reproductive health counseling to the knowledge and attitudes of adolescents about sexual premarital in Lebak Pracimantoro Wonogiri. This study used quasy experiment design with pretest-postest. The sample of the research is 30 adolescents in Lebak Pracimantoro Wonogiri. Statistical analysis using Wilcoxon test with a degree of α = 0.05 significance. The results showed that the respondents knowledge of premarital sex before counseling activities with the most knowledgeable were as many as 29 people (93.5%) and quite as much as 2 people (6.5%). After the counseling activities on premarital sex, there has been an increase in knowledge where good knowledgeable respondents increased to 31 people (100%), there was an increase in scores on 18 respondents and a decrease in scores on 8 respondents. While 5 respondents get the same score between pretes and postes. Statistical test results were obtained that p = 0.02 < α = 0.05 for knowledge and p = 0.043 < α = 0.05 for adolescents attitudes. This demonstrates that reproductive health counseling activities on adolescents influence of knowledge and attitudes about premarital sex.